2002
DOI: 10.1046/j.1474-919x.2002.t01-2-00094_1.x
|View full text |Cite
|
Sign up to set email alerts
|

Effects of food abundance and predictability on body condition and health parameters: experimental tests with the Hooded Crow

Abstract: It has been shown that small passerines can counteract variability of food resources by actively regulating their body reserves through an increase of mass. However, the effects of food predictability on body mass regulation and other body parameters, such as immune functions, in larger species have been little studied. To analyse the response of the Hooded Crow Corvus corone to food abundance and predictability, we performed three experiments with controlled food provisioning under laboratory conditions. Body… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
40
0

Year Published

2008
2008
2020
2020

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 45 publications
(41 citation statements)
references
References 35 publications
(51 reference statements)
1
40
0
Order By: Relevance
“…Considering that T implantation had a negative effect on body mass, and body mass in previous studies has been positively related to immunocompetence (Acquarone et al, 2002;Cucco et al, 2002;Fargallo et al, 2002;Lifjeld et al, 2002), it seems somewhat surprising that T did not have a negative effect on immune response. The reasons for this are unclear; however, it is possible that individuals trade-off condition (as fat reserves) for immunocompetence (McNamara and Buchanan, 2005); the result is no perceived cost of T to immunity but a corresponding cost to condition, as found in our study.…”
Section: L Roberts and Othersmentioning
confidence: 99%
See 1 more Smart Citation
“…Considering that T implantation had a negative effect on body mass, and body mass in previous studies has been positively related to immunocompetence (Acquarone et al, 2002;Cucco et al, 2002;Fargallo et al, 2002;Lifjeld et al, 2002), it seems somewhat surprising that T did not have a negative effect on immune response. The reasons for this are unclear; however, it is possible that individuals trade-off condition (as fat reserves) for immunocompetence (McNamara and Buchanan, 2005); the result is no perceived cost of T to immunity but a corresponding cost to condition, as found in our study.…”
Section: L Roberts and Othersmentioning
confidence: 99%
“…Relating either CORT or T negatively to condition could suggest an indirect cost of maintaining high levels of these hormones. It is also possible that chronic effects of either hormone on body condition will eventually have indirect, negative effects on immunocompetence (Acquarone et al, 2002;Fargallo et al, 2002;Lifjeld et al, 2002).…”
Section: Introductionmentioning
confidence: 99%
“…Although this hypothesis describes an adaptive process, other studies have demonstrated that variable access to food can decrease body mass (Acquarone et al, 2002;Cucco et al, 2002) and growth rate (Boon et al, 1999), and lower plasma testosterone (Bridge et al, 2009). These observations suggest that energy is being mobilized and contradict the adaptive regulation hypothesis.…”
Section: Introductionmentioning
confidence: 99%
“…In birds and mammals, temporal variability in food availability is associated with fattening (Bednekoff and Krebs, 1995), an increase in daily torpor (Munn et al, 2010), increased or stabilized body mass (Witter et al, 1995; Cuthill et al, 2000) and less behavioral activity (Dall and Witter, 1998). These observations are consistent with the adaptive regulation hypothesis (Witter et al, 1995;Fauchald et al, 2004), which describes how animals coping with unpredictable food availability aim to decrease energetic expenditure and attenuate physiology that depletes energy reserves such as CORT secretion, thus promoting energy conservation, which conserves (or even increases) body mass.Although this hypothesis describes an adaptive process, other studies have demonstrated that variable access to food can decrease body mass (Acquarone et al, 2002;Cucco et al, 2002) and growth rate (Boon et al, 1999), and lower plasma testosterone (Bridge et al, 2009). These observations suggest that energy is being mobilized and contradict the adaptive regulation hypothesis.…”
mentioning
confidence: 99%
See 1 more Smart Citation